The Analysis of Synonym Relation Meaning in Kerinci Language: A Semantic Study - Fitrah, Yundi; Afria, Rengki (Universitas Pendidikan Mandalika, 2024)
Synonyms are lexical variants that refer to the same meaning in expressing something in word form. In other cases, synonyms are lexical aspects that support cohesion in discourse which functions as a link between one lingual unit and another. This research explains the analysis of synonym meaning relation in Kerinci language through semantic study. The purpose of this research is to reveal the form of synonym meaning relation in its distribution in Kerinci area. The method used is qualitative, data obtained from oral and written sources, data collection is done by interview, and data analysis is done by semantic lexical technique. The results showed that 94 data concepts (lemma) produced 6-word classes, and 300 synonym data. The six-word classes are noun, verb, adjective, adverb, numeral, and pronoun. From the 300-synonym data, 82 data were found to belong to the TC category, 50 nTC, 138 TnC, and 30 nTnC. Geographically, it was found that the distribution of synonym data in KU was 190 data, 16 KT, 28 KM, and 66 KH. In general, Kerinci language synonyms are categorized as lexical relations because although they can be understood by Kerinci people in speech, they are also basically a form of lexical distribution that refers to vocabulary variants with similar meanings. This happens because of several factors, such as time factor, place/region factor, social factor, nuance factor of meaning. The results of the research are used as a reference and comparison. This research was conducted to reveal the diversity of lexical forms that refer to the same meaning. In other words, identifying the meaning contained in these lexical variants from the point of view of synonyms in semantic studies.